Characterization and identification of a novel chromosomal class C β-lactamase, LAQ-1, and comparative genomic analysis of a multidrug resistance plasmid in Lelliottia amnigena P13 - Li, Anqi; Yan, Chunxia; Zhang, Lei; Liu, Shuang; Feng, Chunlin; Zhang, Linhua; Dong, Fubo; Sheng, Xiusheng; Wang, Lan; Zhang, Yanfang; Lu, Junwan; Xu, Jiefeng; et al. (Frontiers in Microbiology, 2022)
Introduction Lelliottia amnigena, a bacterium usually isolated from natural environments, may cause human infections and has been suggested to be naturally resistant to second- and third-generation cephalosporins. Methods In this study, we determined the whole-genome sequence of an isolate, L. Amnigena P13, isolated from animal farm sewage. On the basis of genome sequence analysis, susceptibility testing, molecular cloning, and enzyme kinetic parameter analysis, we identified a novel chromosome-encoded AmpC β-lactamase, LAQ-1. Results and Discussion blaLAQ-1 is resistant to penicillin G, ampicillin, and several first- to fourth-generation cephalosporins, such as cefazolin, cefoxitin and cefepime. The MIC levels of some β-lactams, such as cefoxitin, cefepime, aztreonam and cefazolin, for the recombinant clone (pUCP24-blaLAQ-1/DH5α) increased by approximately 4- to 64-fold compared with those of the control strain (pUCP24/DH5α). The kinetic properties of LAQ-1, with the highest catalytic activity observed toward piperacillin, were basically the same as those of typical class C β-lactamases, and avibactam had a strong inhibitory effect on its hydrolytic activity. The genetic background of blaLAQ-1 was relatively conserved, and no mobile genetic element (MGE) was found around it. The plasmid pP13-67 of L. amnigena P13 harbored 12 resistance genes [qnrS1, aph(6)-Id, aadA2, sul1, sul2,blaTEM-1, qacEΔ1, dfrA12, tetA and floR] related to different mobile genetic elements within an 22 kb multidrug resistance region. The multidrug resistance region shared the highest nucleotide sequence similarities with those of the chromosomes or plasmids of different bacterial species, indicating the possibility of horizontal transfer of these resistance genes among different bacterial species.